Effect of Packing Density on Rhodopsin Stability and Function in Polyunsaturated Membranes - Niu, Shui-Lin (Biophysical Society, 2005)
Rod outer segment disk membranes are densely packed with rhodopsin. The recent notion of raft or microdomain structures in disk membranes suggests that the local density of rhodopsin in disk membranes could be much higher than the average density corresponding to the lipid/protein ratio. Little is known about the effect of high packing density of rhodopsin on the structure and function of rhodopsin and lipid membranes. Here we examined the role of rhodopsin packing density on membrane dynamic properties, membrane acyl chain packing, and the structural stability and function of rhodopsin using a combination of biophysical and biochemical techniques. We reconstituted rhodopsin into large unilamellar vesicles consisting of polyunsaturated 18:0,22:6n3PC, which approximates the polyunsaturated nature of phospholipids in disk membranes, with rhodopsin/lipid ratios ranging from 1:422 to 1:40. Our results showed that increased rhodopsin packing density led to reduced membrane dynamics revealed by the fluorescent probe 1,6-diphenyl-1,3,5-hexatriene, increased phospholipid acyl chain packing, and reduced rhodopsin activation, yet it had minimal impact on the structural stability of rhodopsin. These observations imply that densely packed rhodopsin may impede the diffusion and conformational changes of rhodopsin, which could reduce the speed of visual transduction.